2013
DOI: 10.1124/dmd.113.053892
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo to In Vitro Effects of Six Bioactive Lignans of Wuzhi Tablet (Schisandra Sphenanthera Extract) on the CYP3A/P-glycoprotein–Mediated Absorption and Metabolism of Tacrolimus

Abstract: We recently reported that Wuzhi tablet (WZ; Schisandra sphenanthera extract) can inhibit P-glycoprotein (P-gp)-mediated efflux and CYP3A-mediated metabolism of tacrolimus (FK506) and thus increase the blood concentrations of FK506. Major active lignans of WZ include schisandrin A, schisandrin B, schisandrin C, schisandrol A, schisandrol B, and schisantherin A. Whether and how these six lignans affect the pharmacokinetics of FK506 remains unclear. Therefore, this study aimed to investigate the effects of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…Therefore, in the enzyme kinetic model of tacrolimus, the demethylation and hydroxylation pathways were usually selected. Nevertheless, STA was found to have poor effect on the transport ratio of tacrolimus in Caco-2 cell [9]. Although SIA inhibited the efflux of tacrolimus completely at the concentration of 100 lM, there was little effect on the transportation of tacrolimus while the concentration of SIA was 50 lM [36], which was much higher than the estimated concentration of SIA in the human intestine (2.7-4.5 lM), which was calculated based on the daily dose of Wuzhi capsule and the reported volume of human gastrointestinal fluid [37].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, in the enzyme kinetic model of tacrolimus, the demethylation and hydroxylation pathways were usually selected. Nevertheless, STA was found to have poor effect on the transport ratio of tacrolimus in Caco-2 cell [9]. Although SIA inhibited the efflux of tacrolimus completely at the concentration of 100 lM, there was little effect on the transportation of tacrolimus while the concentration of SIA was 50 lM [36], which was much higher than the estimated concentration of SIA in the human intestine (2.7-4.5 lM), which was calculated based on the daily dose of Wuzhi capsule and the reported volume of human gastrointestinal fluid [37].…”
Section: Discussionmentioning
confidence: 93%
“…This discrepancy might be explained by the liver microsome of different species and the choice of probe substrate. Furthermore, DDI studies in rats showed that the blood exposure of tacrolimus could be increased to 2.48-and 2.37-fold by STA and SIA, respectively, with an oral dose of 0.024 mmol/kg [9]. Briefly, STA and SIA could inhibit the metabolism of tacrolimus in both in vitro and animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic profile of drugs and drug candidates can be clearly elucidated through combining in vitro incubation mixtures and in vivo animal models . The pharmacokinetics of the six bioactive lignans in WZ were also measured and we found that most of the lignans reached the highest blood concentration at 2 h and nearly eliminated 24 h after an oral dose to rats . However, the complete metabolite profile of WZ and its active lignans remains unclear in vitro and in vivo , and needs to be further clarified to better understand efficacy or toxicity of WZ.…”
Section: Introductionmentioning
confidence: 97%
“…In one such example, co-administration of WWZ has been shown to increase the oral bioavailability of FK506 (Tacrolimus) [53]. WWZ or its constituent compounds have also been shown to increase the bioavailability of cyclosporine A and paclitaxel in animal models [5456]. The metabolism of FK506 mainly occurred in the liver and small intestine via CYP3A [53].…”
Section: Does Pxr Activation Always Cause Increased Drug Metabolism?mentioning
confidence: 99%